2017
DOI: 10.1007/s00066-017-1197-7
|View full text |Cite
|
Sign up to set email alerts
|

Side effects of radiotherapy in breast cancer patients

Abstract: The Internet can give breast cancer patients seeking information on side effects of radiotherapy an overview. However, based on the currently low overall quality of websites and the lack of transparency for the average layperson, we emphasize the value of personal contact with the treating radio-oncologist in order to integrate and interpret the information found online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
0
8
0
2
Order By: Relevance
“…Among 138 full-text tools screened, 96 were excluded based on publication type (51) or date (11), they could not be located (15), lacked any DCIS content (14), were not freely available (9) or were developed by a for-profit organization (3), leaving 39 tools eligible for review (Supplementary File 1). Extracted data are included in Supplementary File 2 [39–80].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among 138 full-text tools screened, 96 were excluded based on publication type (51) or date (11), they could not be located (15), lacked any DCIS content (14), were not freely available (9) or were developed by a for-profit organization (3), leaving 39 tools eligible for review (Supplementary File 1). Extracted data are included in Supplementary File 2 [39–80].…”
Section: Resultsmentioning
confidence: 99%
“…Self-report questionnaire data from 27,491 breast cancer patients between 2007 and 2013 also showed increasing use of the Internet as a source of information, particularly among those younger than 70 years of age, with 10 or more years of formal education, and lower cancer stage [79]. Assessment of 30 English- and 30 German-language web sites on side effects of radiotherapy for breast cancer with DISCERN found that most were poor quality [80]. While Lo et al [37] identified questions important to women with DCIS, we found no prior published studies that developed or evaluated DCIS information tools.…”
Section: Discussionmentioning
confidence: 99%
“…On 1 March 2020 and 13 July 2020, from a Spanish IP address, two Google searches were performed with the terms "Prevencion COVID-19" and "Prevencion Coronavirus". Like in other studies, the first 30 weblinks in Spanish were selected for each search, excluding advertisements [26][27][28]. While using Google, the author was not logged in as a Google user.…”
Section: Methodsmentioning
confidence: 99%
“…Internett brukes også for å finne ut mer om egen eller andre sin sykdom (Fox & Duggan, 2013). Det finnes mange forskjellige nettsider av varierende kvalitet, der mangel på regulering og fagfellevurdering øker sannsynligheten for å få informasjon av dårlig kvalitet (Smart & Burling, 2001;Janssen et al, 2018). Det legges vekt på viktigheten for kreftpasienter å ta kontakt med onkologen på sykehuset for å kunne diskutere og integrere informasjon de finner på nettet (Janssen et al, 2018).…”
Section: Informasjonskilderunclassified
“…Det finnes mange forskjellige nettsider av varierende kvalitet, der mangel på regulering og fagfellevurdering øker sannsynligheten for å få informasjon av dårlig kvalitet (Smart & Burling, 2001;Janssen et al, 2018). Det legges vekt på viktigheten for kreftpasienter å ta kontakt med onkologen på sykehuset for å kunne diskutere og integrere informasjon de finner på nettet (Janssen et al, 2018). I studien av Pahade et al (2018) ble det sett en sammenheng mellom foretrukket informasjonsplattform og utdanningsnivå.…”
Section: Informasjonskilderunclassified